The complete structure of an activated open sodium channel - Altin Sula (Nature Portfolio, 2017)
Voltage-gated sodium (Nav) channels are crucial for action potential initiation in excitable cells. Here the authors present the complete structure of prokaryotic NavMs in a fully open state, providing structural insight into the opening and closure of the channel's intracellular gate.